Mothers' response on Kangaroo Mother Care intervention for preterm infants - Bernie Endyami; Rosalina D. Roeslani; Rinawati Rohsiswatmo; Soedjatmiko Soedjatmiko (Indonesian Pediatric Society, 2009)
Background The low birth weight still remains the main causeof neonatal deaths. Kangaroo Mother Care (KMC) program canprovide a better care for low birth weight newborn infants throughskin-to-skin contact.Objective The aim of this study was to assess factors andresponses from mothers that would influence the re-introductionand re-implementation of KMC at neonatology ward, CiptoMangunkusumo Hospital, Jakarta.Methods This was a prospective preliminary study usingquestionnaires, to mothers oflow birth weight infants who wouldundergo KMC in neonatal ward.Results Most mothers felt sad, guilty, worried, afraid and notconfident when they first saw their babies, thus, they were initiallydoubtful and afraid in the beginning of KMC. But, after KMCwas implemented, most of the mothers found positive effectson mother-infant bonding, maternal affection in love or touch,breastfeeding and mother's confidence in newborn care.Conclusions KMC provides benefits for mothers. Most mothersyield positive response when implementing KMC program to theirinfants.